Scope versus speed: Team diversity, leader experience, and patenting outcomes for firms - Choudhury, Prithwiraj; Haas, Martine R. (Strategic Management Journal, 2018)
[Research Summary: How does the organization of patenting activity affect a firm's patenting outcomes? We investigate how the composition of patenting teams relates to both the scope of their patent applications and the speed with which their patents are approved, by examining the main effects of team members' intra-organizational diversity (based on affiliations with formal organizational units and informal organizational communities) and the moderating effects of team leader experience. We test our moderated mediation model in a sample of 121 teams that filed patents in a Fortune 50 company's India R&D center between 2005 and 2015, using proprietary employee data combined with newly released micro-data from the U.S Patent and Trademark Office (USPTO). Our findings illuminate the microfoundations of innovation in firms by highlighting a trade-off between organizing patenting activity to maximize scope versus speed. Managerial Summary: Patenting is an important strategic tool that firms can use to protect and create value from their innovations. A firm can benefit from filing a patent application that gives it a wider possible set of claims related to an innovation. It can also benefit from faster approval of a patent application by the Patent Office. However, our study shows that there is a trade-off between patent application scope and patent approval speed, which creates tensions for the organization of patenting activities inside firms. In particular, we find that the diversity of a patenting team is positively related to patent scope but negatively related to patenting speed, and that these relationships vary with the experience of the team leader.]